Fitoperifiton composition and structure of the middle and lower basin of the river Cesar, Cesar Department-Colombia - Ana De la parra-Guerra (Revista MVZ Córdoba, 2017)
Objective. The composition and structure of Fitoperifiton the middle and lower basin of the Cesar River and its relationship to the physical and chemical variables were characterized. Materials and methods. Sampling was conducted between February to September 2011. Samples available natural substrates (rocks, sediment and plant debris) were collected, physical and chemical variables in situ and in vivo were measured. Results. 110 Morphospecies classes represented in 9 and 22 orders were found, the Bacillariophyceae had the highest density with 48% (45 species), Cyanophyceae with 35% (18 species), followed by Fragilariophyceae with 7% (9 species), Chlorophyceae 2 % (11 species), Euglenophyceae with 2% (5 species) and Trebouxiophyceae Coscinodiscophyceae with 4% and 1% (respectively 4 and 3 species) and finally with Ulvophyceae 0.00005% (1 species). The most representative Anabaena sp.1 Morphospecies (136.70 Cel/cm2), Oscillatoria Vaucher (129.80 Cel/cm2) and Oscillatoria sp.1 (90.20 Cel/cm2). an analysis of principal components (ACP) where segmentation of some sections of the Cesar River and fitoperifiton was observed to characterize the stations for their peculiarities was made excessive growth of species in areas where they are wastewater discharges high were observed organic matter such as blue-green algae. Conclusions. The Cyanophyceae were negatively associated with oxygen according to the ACC. It was evident that the sector Puente Salguero is characterized by high concentration of organic phosphorus, plus the Fitoperifiton the Cesar River, identified this sector as the most critical point of organic contamination of the system and its influence stations downstream.